A formação de praticantes de Danças Urbanas em cursos de graduação em dança no Brasil de 2007 a 2017 - Santos, Vanessa Garcia (2019)
This research presents a survey of urban dancers who attend or have attended Dance undergraduate courses in Brazil from 2007 to 2017. Through the mixed research method with data collection and concomitant strategy it was possible to obtain data that were analyzed in both quantitative and qualitative ways. The data collection was done through questionnaire composed of 25 dissertative and multiple-choice questions which application obtained 104 responses, of which 95 were considered valid. The theoretical perspective analyzes and interpret the data is the concept of field by the sociologist Pierre Bourdieu. The objective of this work is to observe in what Dance undergraduate courses can be an education context for Urban Dances practitioners, from the students’ point of view. The survey mapped practitioners in the 5 regions of Brazil, in 14 states, and 25 of the 35 institutions that have Dance undergraduate courses in Brazil. It was possible to observe that the number of newcomers and graduates has grown over the years and that the Dance undergraduate courses can contribute in different ways in the education of the Urban Dances practitioners. In addition, it is noted the occurrence of changes in the emergent field of Urban Dances, especially due to the increase of the agents’ symbolic capital when they graduate in Dance.